2012
DOI: 10.1118/1.4736808
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of image registration based measures of regional lung ventilation from dynamic spiral CT with Xe‐CT

Abstract: Purpose: Regional lung volume change as a function of lung inflation serves as an index of parenchymal and airway status as well as an index of regional ventilation and can be used to detect pathologic changes over time. In this paper, the authors propose a new regional measure of lung mechanics-the specific air volume change by corrected Jacobian. The authors compare this new measure, along with two existing registration based measures of lung ventilation, to a regional ventilation measurement derived from xe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 36 publications
3
72
0
Order By: Relevance
“…The majority of the errors were within 3 mm, which is comparable to other studies 15 , 37 and consistent with our previous study (30) . Based on the evaluation results, DM DIR was selected for the ventilation calculations in this study.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The majority of the errors were within 3 mm, which is comparable to other studies 15 , 37 and consistent with our previous study (30) . Based on the evaluation results, DM DIR was selected for the ventilation calculations in this study.…”
Section: Resultssupporting
confidence: 93%
“…Ventilation differences introduced by registration errors can be reduced by smoothing. This evaluation study and previous reports 15 , 18 support the use of ventilation calculated using 4D CT in clinical applications such as radiation treatment planning, 12 , 23 , 24 , 40 , 42 , 43 , 44 , 45 pulmonary function, 15 , 18 and lung disease (22) …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Another possibility to explain the lower correlation values for our study compared to Murphy et al (15) is that the relationship between 4DCT-ventilation and PFT metrics may not be linear (a saturation effects appears in Figure 2) and other mathematical relationships need to be investigated in future work. Our data can be also be compared to other validation work comparing 4DCT-ventilation imaging with other forms of ventilation imaging modalities (6,(16)(17)(18)(19)(20)(21). For example, Ding et al (19) and Reinhardt et al (6) 76.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have attempted to validate 4DCT-ventilation by comparing it against other ventilation imaging modalities such as nuclear medicine ventilation-perfusion (VQ) imaging (16)(17)(18), xenon-CT (6,19), positron emission tomography (20), and magnetic resonance imaging (21). The studies generally found good agreement on a global level with worsening results locally.…”
Section: Introductionmentioning
confidence: 99%